A Critical Reading of The Theories of Underdevelopment and its Current Interpretation (For A Dialectical Concept of Underdevelopment in the Capitalist Age) - سعد فيصل (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Some go as far as to equating or confusing the Underdevelopment in the capitalist age with the Underdevelopment in the ages before it. Which necessarily leads to blurring the reality of contemporary backwardness as a parallel aspect of progress elsewhere within a global capitalist system that arose for the first time in human history against the background and strength of the structural logic of capitalism as a logic of expansion that is not limited by specific national or regional bounders. Underdevelopment within this system and against this background and with this force is a general sociological system that includes all the structures of a backward society. It has always been a structural backwardness of production relations mainly. He expresses himself with complete backwardness and all the political and superstructural infrastructures including the socio-cultural and always by virtue of dialectical necessisty. This is my scientific hypothesis about the reality of Underdevelopment in the capitalist era and its uniqueness in this era compared to cases of Underdevelopment in previous eras. With this hypothesis I will strive (in a way of critical of the another and critical self-awareness) in order to crystallize a structural dialectical concept of Underdevelopment that discovers the flaws and shortcomings of its popular concepts in our countries and around the world.